Integrating Islamic Values Into Digital Character Education: Managing Curriculum Innovation In The Era Of Education 5.0 - Mochammmad Syafiuddin Shobirin; Akhyak; Nur Efendi (International Journal of Education Management and Religion, 2025)
The Industrial Revolution 5.0 era demands that the education system adapt to rapid technological advancements without neglecting character development, particularly within Islamic Religious Education (IRE). This article explores the importance of integrating Islamic values into digital character education as a strategy to shape resilient, adaptive, and globally competitive Muslim generations. Without strong spiritual and moral foundations, digital education risks contributing to a character crisis among students. Therefore, the role of IRE teachers is essential in utilizing technology as a medium to instill Islamic values such as honesty, responsibility, tolerance, and discipline. This study employs a qualitative-descriptive approach with literature review as the primary method. The findings indicate that the integration of Islamic values into digital learning can be achieved through various platforms such as interactive videos, e-learning systems, and educational social media, while maintaining Islamic pedagogical principles. In conclusion, Islamic-based digital character education is not only relevant but also a fundamental necessity in preparing Muslim students to face modern challenges while preserving their moral and spiritual integrity. The implications of this study can serve as a reference for educators and policymakers in designing technology-based IRE curricula.